Answer:
![\frac{5}{13}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B13%7D)
Step-by-step explanation:
Given,
Red marbles = 3,
Green marbles = 10,
So, the total marbles = 3 + 10 = 13,
![\because \text{Probability}=\frac{\text{Favourable outcomes}}{\text{Total outcomes}}](https://tex.z-dn.net/?f=%5Cbecause%20%5Ctext%7BProbability%7D%3D%5Cfrac%7B%5Ctext%7BFavourable%20outcomes%7D%7D%7B%5Ctext%7BTotal%20outcomes%7D%7D)
Since, here replacement is not allowed,
Thus, the probability of getting a green marble and a red marble
= first red and second green + first green second red
![=\frac{3}{13}\times \frac{10}{12}+\frac{10}{13}\times \frac{3}{12}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B3%7D%7B13%7D%5Ctimes%20%5Cfrac%7B10%7D%7B12%7D%2B%5Cfrac%7B10%7D%7B13%7D%5Ctimes%20%5Cfrac%7B3%7D%7B12%7D)
![=2\times \frac{3}{13}\times \frac{10}{12}](https://tex.z-dn.net/?f=%3D2%5Ctimes%20%5Cfrac%7B3%7D%7B13%7D%5Ctimes%20%5Cfrac%7B10%7D%7B12%7D)
![=\frac{30}{78}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B30%7D%7B78%7D)
![=\frac{5}{13}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B5%7D%7B13%7D)
Note : The probability of getting a green marble first and a red marble second
= ![\frac{10}{13}\times \frac{3}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B10%7D%7B13%7D%5Ctimes%20%5Cfrac%7B3%7D%7B12%7D)
![=\frac{30}{156}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B30%7D%7B156%7D)
![=\frac{5}{26}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B5%7D%7B26%7D)
Answer:
The values from least to greatest would be 202, 245, 245, 254, 276
The mean would be 244.4
The median would be 245
The mode would be 245
Step-by-step explanation:
To find the mean, you add all the numbers together and divide that sum by the number of numbers. In this case, you add all the numbers together and you get 1222. Next, you divide that by 5 because there are 5 numbers. To find the median, you order the numbers from least to greatest and find the middle number. For this question, the answer would be 245. Lastly, to find the mode you look for the number that appears the most. In this case it's 245.
Answer:
f(x)= 3x-4
f(-1)= 3*-1-4
f(-1)= 2-4
f(-1)= -2
f(x)= 3x-4
f(3)= 3*3-4
f(3)= 9-4
f(3)=5
f(x)= 3x-4
f(1)= 3*1-4
f(1)= 3-4
f(1)= -1
Step-by-step explanation:
Answer:
12
Step-by-step explanation:
in this problem there is A+b=15
A=9
B=12
Answer:
- 7y +3 =-25
-7y=-25—3
-7y=-28
-7y÷-7= -28÷-7
y=4
Step-by-step explanation:
Take +3 to the side so that your variable and a constant is on their own sides. When a number goes over the equals sign the sign changes at becomes the inverse that's why l said - 3. You now calculate - 25—3 equals 28 then divide by 7 to find y and your y is 4.